Fungal and substrate-associated factors affecting lignocellulolytic mushroom cultivation on wood sources available in South African [i.e. Africa] - Da Serra, Maria Fatima (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1997)
Vast- quantities of lignocellulosic materials, representing potential substrates for the cultivation of speciality mushrooms, are produced annually in South Africa. A number of these materials are derived as waste products of the timber and agricultural industries, e.g. Maranti (Shorea spp.) and Port Jackson Willow (Acacia longifolia) respectively. The screening of various wood-degrading fungi, which are cultivated worldwide for their production of speciality mushrooms, indicated that under the environmental conditions considered, certain species were adapted to cultivation on these lignocellulosic wastes (Pleurotus species) whereas others were not (Lentinus edodes and Flammulina velutipes). Furthermore, intra- and interspecies specific differences in the growth and production potential of the various lignocellulolytic fungi investigated on synthetic and natural medium were discovered. Biochemical and genetical investigations of these strains indicated differences between and within species which were often significant. Species varied qualitatively and quantitatively in the lignocellulolytic enzymes produced, which was loosely correlated with productivity on the different media investigated. Genetical studies, using RAPD fingerprinting, indicated that the Pleurotus genus is highly variable which supports the observed differences in growth, yield and enzymatic activity between different strains and species.
Keywords: Lignocellulose; Mushroom culture; Cultivated mushroom; Fungi -- Cultures and culture media; Fungi -- Biotechnology; Mushroom culture -- South Africa